Um modelo de visão computacional para identificação do estágio de maturação e injúrias no pós-colheita de bananas (Musa sapientum) - Tezuka, Érika Sayuri (2009)
This dissertation presents the development of a computer vision system for bananas (Musa sapientum) analysis in post-harvest stage based on digital image processing techniques. The development used considerations about image acquisition, pre-processing, identification based on texture, percentage of brown spots and injuries on the fruits and classification of its maturity levels. The validation has been developed considering geometric patterns generated in laboratory, as well as real fruits. With the texture map it was possible to identify the existence of brown spots or injuries in a specific region of the images. The assessment of the level of maturation was performed considering both human observers and the computer vision system. The average of identification level of maturity was equal to 50% for human observers and 100% for computer vision. The results show identification rates of 80.40% for brown spots on the single image of banana, 97.70% for brown spots on the images of bundle of bananas, 97.80% for injuries for the set of single image of banana, and 75.30% for hand injuries considering the images of bundle of bananas. Besides, the method presents application for quality assessing of fruits in the post-harvest procedures.